Unusual case of Marchiafava-Bignami disease presenting as axial hypotonia - Miletić Drakulić, Svetlana D.; Jevdjić, Jasna; Aleksić, Dejan; Tončev, Gordana (Vojnosanitetski pregled, 2021)
Introduction. Marchiafava-Bignami disease is a rare disorder mostly associated with chronic heavy alcohol consumption that results in progressive demyelination and necrosis of the corpus callosum. Case report. We reported a 35-year-old woman with a history of alcohol consumption and malnutrition. Neurological examination revealed axial hypotonia, dysarthric speech and lack of motor coordination. The brain multislice computed tomography imaging demonstrated hypodense lesion of the corpus callosum. On the basis of her history, clinical features and imaging studies, the diagnosis of an acute form of Marchiava-Bignami disease was made. Definite diagnosis was confirmed at autopsy. Conclusion. Marchiafava-Bignami disease is of a medical emergency and early recognition and early aggressive treatment are critical for a good clinical outcome. To our knowledge, this is the first case of Marchiafava-Bignami disease presented with axial hypotonia.